O društvenoj ulozi katolicizma u Banskoj Hrvatskoj potkraj 19. i na početku 20. stoljeća - Strecha, Mario (Array, 2003)
O društvenoj ulozi katolicizma u Banskoj Hrvatskoj potkraj 19. i na početku 20. stoljeća